The Prognosis and Immune Checkpoint Blockade Efficacy Prediction of Tumor-Infiltrating Immune Cells in Lung Cancer - Liu, Xiangzheng; Shang, Xueqian; Li, Jian; Zhang, Shijie (Frontiers in Cell and Developmental Biology, 2021)
Backgrounds: The high morbidity and mortality of lung cancer are serious public health problems. The prognosis of lung cancer and whether to apply immune checkpoint blockade (ICB) is currently an urgent problem to be solved. Methods: Using R software, we performed Kaplan-Meier analysis, Cox regression analysis, functional enrichment analysis, Spearman correlation analysis and the ssGSEA analysis. Results: On the TIMER2.0 website, we calculated the abundance of tumor-infiltrating immune cells (TIICs) of LUAD and LUSC patients. B cell and myeloid dendritic cell (DC1) were independent prognostic factors for LUAD and LUSC patients, respectively. Enrichment analysis confirmed that genes highly related to B cell or DC1 were closely related to the immune activation of lung cancer patients. In terms of adaptive immune resistance markers, CD8A, CD8B, immunomodulators (immunostimulants, MHC, receptors and chemokines), immune-related pathways, tumor microenvironment (TME) score and TIICs, high B cell/DC1 infiltration tissues was inflamed, immune-activated, and might benefit more from the ICB. Genes most related to B cell (CD19, TLR10 and FCRLA) and DC1 (ITGB2, LAPTM5 and SLC7A7) partially clarified the roles of B cell/DC1 in predicting ICB efficacy. Among the 186 KEGG pathways, there were 3 and 4 KEGG pathways, which partially explained the molecular mechanisms by which B cell and DC1 simultaneously predicted the prognosis and efficacy of immunotherapy, respectively. Among 5 immune subtypes, the abundance of B cell/DC1 and expression of 6 hub genes were higher in immune C2, C3 and C6. Conclusion: B cell and DC1 could predict the prognosis and ICB efficacy of LUAD and LUSC patients, respectively. The 6 hub genes and 7 KEGG pathways might be novel immunotherapy targets. Immune C2, C3 and C6 subtypes of lung cancer patients might benefit more from ICB therapy.